Pattápio Silva (1880-1907): uma abordagem interpretativa de sua música em forma de dança e de livre fantasia - Rubem Eloy Schuenck (2012)
This paper focuses on the works of the flutist and composer Pattápio Silva (1880-1907), and aims to help those who want make pieces by this Brazilian flute master part of his or her repertoire. His works were divided into two groups: dance form, where we found two waltzes, one mazurka and a polka, and free-fantasy, where the composer did not follow any pre-determined form. Recognized as a great flute virtuoso during his life, Pattápio still do not have the same respect related to his compositions. This study features technical and interpretive suggestions that can help the performance of the pieces. Through analyses we could note that Pattápio had a refined composition technique, including his piano parts.